Augmented thrombin formation is related to circulating levels of extracellular vesicles exposing tissue factor and citrullinated histone-3 in anti-neutrophil cytoplasmic antibody-associated vasculitides - Jonasdottir, Asta Dogg; Manojlovic, Milena; Vojinovic, Jelena; Nordin, Annica; Bruchfeld, Annette; Gunnarsson, Iva; Mobarrez, Fariborz; Antovic, Aleksandra (Frontiers in Medicine, 2023)
Objectives To study circulating myeloperoxidase (MPO)-positive extracellular vesicles (MPO+EVs) exposing citrullinated histone-3 (H3Cit), tissue factor (TF), and plasminogen (Plg) in association to thrombin generation in patients with anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV). Methods We have involved well-characterized patients with AAV together with population-based controls. Flow cytometry was used to assess the levels of MPO+EVs in citrated plasma. MPO+EVs were phenotyped by anti-MPO-antibodies together with anti-CD142 (anti-TF), anti-H3Cit, and anti-Plg antibodies. A modified Calibrated Automated Thrombogram (CAT) assay was utilized to measure thrombin generation in plasma initiated by EVs-enriched pellets. The activity of AAV was evaluated with the Birmingham Vasculitis Activity Score (BVAS). Results This study comprised 46 AAV patients, 23 in the active stage of the disease and 23 in remission, as well as 23 age- and sex matched population-based controls. Augmented levels of all investigated MPO+ EVs were found in active AAV patients in comparison to the subgroup of patients in remission and controls. Thrombin generation, measured by endogenous thrombin potential (ETP) and peak of thrombin formation, was higher in plasma when triggered by EVs-enriched pellet from AAV patients. ETP and peak were associated with the levels of MPO+TF+ and MPO+H3Cit+ EVs. Additionally, MPO+TF+ EVs correlated with the disease activity evaluated with BVAS. Conclusion Augmented thrombin generation is found in AAV patients regardless of disease activity and is associated with higher exposure of TF and H3Cit on MPO+EVs. This may contribute to the increased risk of thrombosis seen in AAV patients.